2010
DOI: 10.1007/s10620-010-1202-9
|View full text |Cite
|
Sign up to set email alerts
|

Generating Ceramide from Sphingomyelin by Alkaline Sphingomyelinase in the Gut Enhances Sphingomyelin-Induced Inhibition of Cholesterol Uptake in Caco-2 Cells

Abstract: Background Sphingomyelin (SM) is present in dietary products and cell plasma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
(41 reference statements)
0
23
0
Order By: Relevance
“…It has also been suggested that ceramide, the hydrolytic product of SM, inhibits intestinal cholesterol uptake [4]. Since the degradation of ceramide along the gastrointestinal tract is relatively slow and inefficient, it is possible that the inhibitory effect of ceramide on cholesterol absorption could be quite significant [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that ceramide, the hydrolytic product of SM, inhibits intestinal cholesterol uptake [4]. Since the degradation of ceramide along the gastrointestinal tract is relatively slow and inefficient, it is possible that the inhibitory effect of ceramide on cholesterol absorption could be quite significant [19].…”
Section: Discussionmentioning
confidence: 99%
“…SM is a sphingolipid found in foods such as milk and eggs. Purified SM has been shown to inhibit cholesterol absorption in a number of acute in vitro [4] and in vivo [5][8] studies. A recent study reported plasma and hepatic lipid lowering effects in Zucker fatty rats fed a low-fat chow diet supplemented with chicken skin-derived SM for 6 weeks [9].…”
Section: Introductionmentioning
confidence: 99%
“…Noh and Koo compared the inhibitory effects of SM from different sources, milk and egg, on cholesterol absorption, and found that milk SM had a stronger inhibitory effect probably due to higher saturation degree and longer chain of fatty acyl group in SM [98]. Feng found that ceramide, the hydrolytic product of SM, had a stronger inhibitory effect on cholesterol uptake in intestinal cells [191]. The possible mechanisms of inhibitory effect of phospholipids are discussed in Section 5.2.…”
Section: The Relationship Between Egg Intake and Cvd Risksmentioning
confidence: 99%
“…This aforementioned inhibitory effect is a result of direct interaction between SM and cholesterol leading to a decreased cholesterol thermodynamic activity [53]. Moreover, Feng et al [54] showed that cholesterol absorption is also inhibited by ceramide formed from SM through the activation of alkaline sphingomyelinase [54]. Those authors proved that ceramide, as an inhibitor of cholesterol absorption, is more effective than SM [54].…”
Section: Physiological Role Of Sphingolipids In Gastrointestinal Tmentioning
confidence: 99%
“…Moreover, Feng et al [54] showed that cholesterol absorption is also inhibited by ceramide formed from SM through the activation of alkaline sphingomyelinase [54]. Those authors proved that ceramide, as an inhibitor of cholesterol absorption, is more effective than SM [54]. Moreover, cholesterol uptake by intestinal cells is suppressed by sphingosine, but it is less effective than SM and ceramide [55].…”
Section: Physiological Role Of Sphingolipids In Gastrointestinal Tmentioning
confidence: 99%